Hepatic PPARγ and LXRα independently regulate lipid accumulation in the livers of genetically obese mice - Matsusue, Kimihiko (FEBS Lett, 2014)
The nuclear hormone receptors liver X receptor α (LXRα) and peroxisome proliferator-activated receptor γ (PPARγ) play key roles in the development of fatty liver. To determine the link between hepatic PPARγ and LXRα signaling and the development of fatty liver, a LXRα-specific ligand, T0901317, was administered to normal OB/OB and genetically obese (ob/ob) mice lacking hepatic PPARγ (Pparγ(∆H)). In ob/ob-Pparγ(∆H) and OB/OB-Pparγ(∆H) mice, as well as ob/ob-Pparc(WT) and OB/OB-Pparγ(WT) mice, the liver weights and hepatic triglyceride levels were markedly increased in response to T0901317 treatment. These results suggest that hepatic PPARγ and LXRα signals independently contribute to the development of fatty liver.